2016
DOI: 10.1123/iscj.2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

Over Egging the Pudding? Comments on Ojala and Thorpe

Abstract: In a recent paper in ISCJ, Ojala and Thorpe offered a culturally based observation that questions the role and application of coaching in action sports. Their critique is focused on the action sport of snowboarding which, despite its’ comparatively recent inclusion in the Olympics, retains a different, almost collaborative rather than competitive culture more akin to other action sports such as skateboarding and surfing. Ojala and Thorpe then present Problem Based Learning (PBL) as the solution to many of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Coaching that does not reflect the culture of a particular sport may also be rejected (see Ojala & Thorpe's study of elite snowboarders, 2015). It seems likely that this is a rejection of poor coaching rather than of all coaching (D. Collins, Collins & Willmott, 2016). In short, the rejection of coaching represents a failure to individualise the process.…”
Section: Individualisation In Adventure Sport Coachingmentioning
confidence: 99%
“…Coaching that does not reflect the culture of a particular sport may also be rejected (see Ojala & Thorpe's study of elite snowboarders, 2015). It seems likely that this is a rejection of poor coaching rather than of all coaching (D. Collins, Collins & Willmott, 2016). In short, the rejection of coaching represents a failure to individualise the process.…”
Section: Individualisation In Adventure Sport Coachingmentioning
confidence: 99%
“…The need for cultural sensitivity and alignment is demonstrated by Objala and Thorpe (2015) who identified that some nature sports participants reject formal highly structured facilitation. While it would be an oversimplification to say all participants reject formal approaches to the design and facilitation of learning (Collins, Wilmot, & Collins 2016), this does support a need for breadth and range in facilitation skills.…”
Section: Facilitating Learning In Nature Sports?mentioning
confidence: 99%
“…Specifically, a comparative dearth of investigation, together with this recent but powerful change, has effectively negated what little data were already available (e.g. Collins, Collins & Willmott, 2016). Such information is essential to the coach for effective planning, monitoring, and direction of athlete progression (cf.…”
Section: A Retrospective Analysis Of Trick Progression In Elite Freesmentioning
confidence: 99%